Impact of sarcopenia on surgical site infection after restorative proctocolectomy for ulcerative colitis - Fujikawa, Hiroyuki; Araki, Toshimitsu; Okita, Yoshiki; Kondo, Satoru; Kawamura, Mikio; Hiro, Junichiro; Toiyama, Yuji; Kobayashi, Minako; Tanaka, Koji; Inoue, Yasuhiro; Mohri, Yasuhiko; Uchida, Keiichi; et al. (Surgery today (Tokyo, Japan), 2017)
Purpose The coexistence of sarcopenia is associated with postoperative complications, including infection after abdominal surgery. We evaluated the association between sarcopenia and surgical site infection (SSI) after surgery for ulcerative colitis. Methods The subjects of this retrospective study were 69 patients who underwent restorative proctocolectomy with perioperative abdominal computed tomography (CT). Sarcopenia was diagnosed by measuring the cross-sectional area of the right and left psoas muscles as the total psoas muscle area on CT images. We assessed whether sarcopenia was associated with SSI and clinical factors, including nutritional and inflammatory markers. Results The lowest quartiles defined as sarcopenia in men and women were 567.4 and 355.8 mm 2 /m 2 , respectively. According to this classification, 12 men and 6 women had sarcopenia. Patients with sarcopenia had a lower body mass index ( p = 0.0004) and a higher C-reactive protein concentration ( p = 0.05) than those without sarcopenia. SSIs were identified in 12 patients (17.3 %) and included six pelvic abscesses and seven wound infections. According to multivariate analysis, sarcopenia was an independent risk factor for SSI (odds ratio = 4.91, 95 % confidence interval 1.09–23.5, p = 0.03). Conclusion Sarcopenia is predictive of SSI after pouch surgery for ulcerative colitis.